EARLY RECURRENCE OF WELL-DIFFERENTIATED ENDOMETRIAL CANCER (A CASE REPORT) - N. E. Levchrnko; Yu. S. Sidorenko (Сибирский онкологический журнал)
Endometrial cancer is the 6-th most common malignancy in women worldwide, accounting for about 4.8 % of all female cancers. The treatment of recurrent endometrial cancer remains a major challenge. Some endometrial cancer recurrences, for example vaginal stump recurrence, are reported to be effectively treated with surgical resection and radiation therapy. Early recurrence of early-stage well-differentiated endometrial cancer is uncommon. Case report. Herein we report a rare case of recurrent well-differentiated endometrial cancer in a 65-year-old woman. The patient had recurrence 10 months after laparoscopic hysterectomy with bilateral salpingo-oophorectomy. Recurrent endometrial tumor with extension into the rectosigmoid colon, urinary bladder and the right ureter manifested itself clinically with severe pain requiring the use of opioids. The recurrent tumor was removed. Resection of the bladder, left ureter and upper ampular rectum was followed by anastomosis. The patient received multiple cycles of chemotherapy. Conclusion. Compliance with the principles of ablastics during the laparoscopic or laparotomic surgery helps to avoid recurrence in patients with prognostically favorable cancer. In case of recurrence, combined operations are the only possible chance of improving survival of patients with locally advanced or recurrent tumors, which are insensitive to chemoradiotherapy.